1998
DOI: 10.1002/(sici)1097-0215(19980529)76:5<729::aid-ijc19>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Drug binding to P-glycoprotein is inhibited in normal tissues following SDZ-PSC 833 treatment

Abstract: Rats were treated with daily injections of SDZ‐PSC 833 (PSC) to study the interaction of this potent modulator of multidrug resistance (MDR) with P‐glycoprotein (P‐gp) expressed in normal tissues. After 2 days of treatment, the level of P‐gp expression, detected by Western blot analysis, was not modified in renal brush border membranes (BBMs) and brain capillaries. However, the amount of P‐gp detected with the photoaffinity probe [125I]‐arylazidoprazosin (IAAP) was decreased in both tissues, suggesting that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…This study also showed that cyclosporin A induced overexpression of Pgps, in agreement with Jette et al [33,34]. In contrast, expression of Mdr2, Mrp2 and Bsep, which are important carrier proteins for biliary secretion, was not induced.…”
Section: Discussionsupporting
confidence: 92%
“…This study also showed that cyclosporin A induced overexpression of Pgps, in agreement with Jette et al [33,34]. In contrast, expression of Mdr2, Mrp2 and Bsep, which are important carrier proteins for biliary secretion, was not induced.…”
Section: Discussionsupporting
confidence: 92%
“…Efflux pump inhibition can be mediated by numerous mechanisms. Especially SMIs are capable of inhibiting efflux pump by blocking or modifying efflux pump drug-binding sites ( 79 ). However, efflux pumps display various drug-binding sites, so that a targeted development of SMIs inhibitors remains difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Multidrug resistance (MDR) has been a significant problem in cancer chemotherapy, and overcoming the MDR phenomenon is a crucial aspect of cancer research. MDR and modulation of MDR has been intensively studied in vitro and in vivo 1–4 . The MDR phenotype is characterized by a low free intracellular cytotoxic drug concentration in comparison with its corresponding drug‐sensitive cells.…”
Section: Introductionmentioning
confidence: 99%